Family-centered caregiving from hospital to home: Coping with trauma and building capacity with the HOPE for Families model - Anna Newcomb; L Gordon Moore; Holly Matto (The Beryl Institute, 2018)
Informal caregivers and families play a significant role in the recovery process of trauma survivors. However, the needs and outcomes of orthopedic caregiving family members in the months following traumatic injury have received almost no attention in the literature. Our study sought to understand the factors impacting orthopedic trauma families' experience and their ability to cope and provide care post-acute hospitalization. Based on these findings, we designed a hospital-based program to enhance family coping and adjustment post-discharge. Caregivers (N=12) of patients with orthopedic trauma injury engaged in three in-depth semi-structured face-to-face interviews to identify their most salient concerns. Once home, subjects described caregiving life at home, their coping strategies for managing the patient's recovery, and help they received from formal and informal sources. Analysis of the qualitative data found that trauma care lacks a unified system of coordination after the patient's return home. Thus, the role of "secondary caregivers" - longtime friends, family members, church groups, neighbors - was significant. Without an organized system of support and information, the caregivers in our study turned to their established communities for comfort and assistance. Conclusions: Based on these findings, we designed a family caregiver program, Holistic Orthopedic Patient-centered Engagement (HOPE for Families), to support families in this early transition, and to enhance collective and continuous caregiving capacity. HOPE for Families uses peer mentors as "central care organizers" to identify and engage the family's secondary caregivers system, using the HOPE Care Planning tool to identify stressor/demands and caregiver resources to meet anticipated needs.